Quantifying Urban Street Transformation: Integrating Informal Economic Activity Intensity (IIAEI) and Spatial Occupation Ratio (SOR) in Medan City - I Gede Wyana Lokantara; Rafika Hilmi Nasution; Lia Lisyati (Jurnal Perkotaan, 2026)
Informal economic activities significantly influence the spatial and functional transformation of urban street corridors; however, their quantitative impact has not been examined in depth. This study analyzes the restructuring of street space by informal activities by integrating spatial pattern analysis (linear, spot, and mixed) with two quantitative indicators: the Informal Economic Activity Intensity Index (IIAEI) and the Spatial Occupation Ratio (SOR). Empirical data from three urban corridors in Medan City demonstrate that street space transformation occurs systematically through the interaction between activity intensity and spatial distribution. The findings indicate a non-linear relationship between activity intensity and spatial occupation, with SOR reaching up to 100 percent in several corridor segments. Concentrated activities result in high spatial pressure even at lower intensity levels, whereas dispersed activities lead to lower pressure despite higher activity counts. This interaction yields three distinct corridor typologies: high-pressure corridors, concentration-based hotspots, and transitional corridors. This study introduces a novel quantitative framework that operationalizes the relationship between informal economic activities and street space transformation by integrating IIAEI and SOR, enabling a measurable and comparative assessment of spatial pressure. The integration of IIAEI and SOR enables an objective, comparative assessment of spatial pressure. The results underscore the need to transition from control-oriented policies to integrative, data-driven approaches, thereby positioning urban street space as an adaptive and inclusive socio-economic environment.